Determinants of Nurse Case Manager Role Function in Aceh Province General Hospitals - Juanda, Andri; Kamil, Hajjul; Marthoenis, Marthoenis (Advances In Social Humanities Research, 2025)
The role of nurse case managers at Aceh Province General Hospitals is still developing and requires improvement, especially in cross-sector coordination and providing more intensive training for healthcare workers. This study aims to identify the determinants related to the role function of nurse case managers at Aceh Province General Hospitals. The study employed a quantitative analytical design with a cross-sectional approach. The sample consisted of 61 nurse case managers working at type B public hospitals in Aceh Province. Data were collected using a questionnaire developed by the researcher based on relevant literature. Data analysis was conducted descriptively and inferentially using the chi-square test and binary logistic regression. The results showed that perceptions of self-skills and knowledge, as well as the role within the managed care organization, are significantly associated with the role function of nurse case managers. The perception of self-skills and knowledge was identified as the most influential factor. It is recommended that nurse case managers enhance their self-perception of skills and knowledge to improve their role effectiveness in hospitals.